2019
DOI: 10.1002/eem2.12058
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Transition Metal Carbides and Nitrides (MXenes): Synthesis, Properties, and Electrochemical Energy Storage Applications

Abstract: A family of 2D transition metal carbides and nitrides known as MXenes has received increasing attention since the discovery of Ti3C2 in 2011. To date, about 30 different MXenes with well‐defined structures and properties have been synthesized, and many more are theoretically predicted to exist. Due to the numerous assets including excellent mechanical properties, metallic conductivity, unique in‐plane anisotropic structure, tunable band gap, and so on, MXenes rapidly positioned themselves at the forefront of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
205
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 417 publications
(206 citation statements)
references
References 235 publications
(416 reference statements)
1
205
0
Order By: Relevance
“…This makes the strip transition from a “C-shape” to an “I-shape,” followed by inverted “C-shape.” The contribution of MXene in the photothermal behavior of MXene/NIPAm is crucial, as the sample without MXene did not show any bending changes during the experiment. MXene is known for its high heat conductivity [ 52 ]. This increases the sensitivity/efficiency of the photothermal process.…”
Section: Resultsmentioning
confidence: 99%
“…This makes the strip transition from a “C-shape” to an “I-shape,” followed by inverted “C-shape.” The contribution of MXene in the photothermal behavior of MXene/NIPAm is crucial, as the sample without MXene did not show any bending changes during the experiment. MXene is known for its high heat conductivity [ 52 ]. This increases the sensitivity/efficiency of the photothermal process.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the power delivery (P) can be calculated using this equation P = V 2 /4R, where R is the equivalent series resistance of the supercapacitor. Self-standing MXenes are among the most promising materials for supercapacitors due to their excellent electrical conductivity, mechanical flexibility, high surface area, and high capacitance [ 24 , 69 , 70 ]. Thereby, few reviews emphasized the utilization of MXenes as supercapacitors, which showed that self-standing Ti 3 C 2 T x is the most studied MXenes [ 71 , 72 , 73 ].…”
Section: Self-standing Mxene As Electrode For Supercapacitorsmentioning
confidence: 99%
“…The W 2 C/WS 2 _2h, W 2 C/WS 2 _4h, and W 2 C/WS 2 _12h NFs showed the charge and discharge capacities of 595.2 and 935.2 mAh g −1 , 751.8 and 1040.5 mAh g −1 , 717.7 and 953.5 mAh g −1 , respectively. It has been reported that carbide materials are promising candidates for energy storage applications [ 41 ]. In this study, the addition of W 2 C to the WS 2 NF sample improved its storage capacity.…”
Section: Resultsmentioning
confidence: 99%